2015
DOI: 10.1080/19336896.2015.1115945
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the cause of initially reactive bovine brains on rapid tests for BSE

Abstract: Bovine spongiform encephalopathy (BSE) is an invariably fatal prion disease of cattle. The identification of the zoonotic potential of BSE prompted safety officials to initiate surveillance testing for this disease. In Canada, BSE surveillance is primarily focused on high risk cattle including animals which are dead, down and unable to rise, diseased or distressed. This targeted surveillance results in the submission of brain samples with a wide range of tissue autolysis and associated contaminants. These cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…In the latter, skulls of cattle were defrosted with hot steam in winter to facilitate sampling of the medulla oblongata. In Canada, individual decomposed brainstem samples of fallen stock revealed a similar PrP res profile in Western immunoblot as the Swiss cases (Dudas, James, Anderson, & Czub, 2015). In that study, the authors further characterized the status of the samples using a variety of test platforms, including ones that were not relying on PK digestion, such as an affinity ligand-based immunoassay (IDEXX HerdChek BSE Antigen Test) and an ELISA test that used mild PK digestion in combination with PrP res precipitation (Bio-Rad TeSeE ELISA).…”
Section: Discussionmentioning
confidence: 70%
“…In the latter, skulls of cattle were defrosted with hot steam in winter to facilitate sampling of the medulla oblongata. In Canada, individual decomposed brainstem samples of fallen stock revealed a similar PrP res profile in Western immunoblot as the Swiss cases (Dudas, James, Anderson, & Czub, 2015). In that study, the authors further characterized the status of the samples using a variety of test platforms, including ones that were not relying on PK digestion, such as an affinity ligand-based immunoassay (IDEXX HerdChek BSE Antigen Test) and an ELISA test that used mild PK digestion in combination with PrP res precipitation (Bio-Rad TeSeE ELISA).…”
Section: Discussionmentioning
confidence: 70%
“…A weak signal may show a single diglycosylated band or a weak signal for diglycosylated and monoglycosylated bands with the absence of an unglycosylated band [ 21 , 76 ]. In very weak positive samples, the ultracentrifugation step prior to loading the samples onto an SDS-PAGE gel considerably enhances the concentration of PrP Sc , leading to a much more intense Western blot signal [ 88 ]. The use of the correct brain sample is important for correct diagnosis.…”
Section: Western Blot Methodsmentioning
confidence: 99%
“…In field conditions, brainstem samples are often autolyzed and contaminated with bacteria and other debris (feces, soil, hair). Obviously, these factors have an impact on the quality of the sample and affect the performance of the diagnostic test and the results generated [ 88 ]. Meloni et al revealed that four rapid tests (Enfer TSE Kit, Bio-Rad TeSeE test, Prionics ® -Check-LIA test, and IDEXX HerdCheck BSE Antigen Test Kit EIA) can be considered as well-running diagnostics tools regardless of tissue quality [ 100 ].…”
Section: Eu-approved Rapid Testsmentioning
confidence: 99%
“…As in atypical BSE, new types could have different characteristics and pose different risks to the health of animals and humans. Several countries have reported low level reactivity in samples submitted for BSE surveillance [32][33][34] . There is suggestion that these cases represent a yet to be identified prion disease of cattle 32) , but also proposed alternative explanations 33) .…”
Section: New Atypical Bse Strains?mentioning
confidence: 99%
“…Several countries have reported low level reactivity in samples submitted for BSE surveillance [32][33][34] . There is suggestion that these cases represent a yet to be identified prion disease of cattle 32) , but also proposed alternative explanations 33) . To definitively determine if these animals are infected with a prion disease that is transmissible, brain homogenates were intra-cranially inoculated into transgenic mice and cattle.…”
Section: New Atypical Bse Strains?mentioning
confidence: 99%